Altered expression of kisspeptin, dynorphin, and related neuropeptides in polycystic ovary syndrome: A cross-sectional study - Andon Hestiantoro; Rachellina Noor Al Maghfira; Ratna Fathmasari; Ririn Rahmala Febri; Ericko Ongko Joyo; Raden Muharam; Gita Pratama; Anom Bowolaksono (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Since kisspeptin (KISS1) in the hypothalamus is affected by the inhibitory effect of dynorphin, it raises questions about the controlled balance of these 2 neuropeptides in women with and without polycystic ovary syndrome (PCOS). Objective: This study compares the expression levels of KISS1, dynorphin, neurokinin-B, leptin, and neuropeptide-Y in women with and without PCOS. Materials and Methods: In this cross-sectional study, the peripheral blood samples of 20 women with PCOS and 20 women without PCOS who referred to Yamin Kencana Clinic, Cipto Mangunkusumo hospital, Jakarta, Indonesia were enrolled from August-December 2022. mRNA relative expression of genes related to the central factors associated with PCOS, such as leptin, neuropeptide-Y, KISS1, tachykinin-3, and prodynorphin (PDYN), in PCOS and non-PCOS populations were examined. Gene quantification was carried out by the quantitative polymerase chain reaction method. Results: The KISS1/PDYN ratio was significantly higher in the PCOS group than in the control group (p = 0.02), and the PDYN was lower in the PCOS group than the control group (p < 0.001). Moreover, the positive correlation between KISS1 and the KISS1/PDYN ratio was significantly stronger in the PCOS group than in the control group (R = 0.93; p < 0.001 vs. R = 0.66, p < 0.001). Conclusion: Our results suggest that an increased KISS1/PDYN ratio in PCOS women is related to diminished dynorphin expression. Low expression of the gene encoding dynorphin and a high KISS1/PDYN ratio is highly specific to PCOS.